Piezoresistivity of resin-impregnated carbon nanotube film at high temperatures. (2nd July 2018) - Li, Min; Zuo, Tianyi; Wang, Shaokai; Gu, Yizhuo; Gao, Limin; Li, Yanxia; Zhang, Zuoguang
Abstract: This paper presents the development of a continuous carbon nanotube (CNT) composite film sensor with a strain detecting range of 0%–2% for structural composites. The strain-dependent resistance responses of continuous CNT film and its resin-impregnated composite films were investigated at temperatures as high as 200 °C. The results manifest that impregnation with resin leads to a much larger gauge factor than pristine film. Both the pristine and composite films show an increase in resistivity with increasing temperature. For different composite films, the ordering of gauge factors is consistent with that of the matrix moduli. This indicates that a resin matrix with higher modulus and strong interactions between CNTs/CNT bundles and the resin matrix are beneficial for enhancing the piezoresistive effect. The CNT/PAA composite film has a gauge factor of 4.3 at 150 °C, an order of magnitude higher than the metal foil sensor. Therefore, the CNT composite films have great potential for simultaneous application for reinforcement and as strain sensor to realise a multifunctional composite.